Application of the Abbey pain scale for assessment of acute perioperative pain in elderly patients with impaired communication following a femur fracture - Jerleković, Marica; Domijan, Marina; Bareta, Saša; Djulabić, Luka; Mićković, Vlatko; Lončar, Zoran, liječnik (2020)
Pain resulting from physical trauma and surgical procedures is very strong. In elderly patients, especially those with impaired communication or cognitive damage, it is assessed rarely or not at all. The importance of pain assessment is reflected in quality supervision and adequate treatment which decrease complications and speed up recovery. The aim of the study was to determine the metric characteristics (reliability and validity) of the Abbey Pain Scale on a population of elderly patients with impaired communication in Croatia and to demonstrate the correlation between the assessed acute pain level and analgesia efficacy. The sample consisted of 31 patients above the age of 65 hospitalized after a femur fracture at the Department of Traumatology, Sestre Milosrdnice University hospital, Zagreb, Croatia. The Abbey Pain Scale and Visual Analogue Scale were used for pain assessment. The patients’ mental status was evaluated using Mini-Mental State Examination. The data was processed using Chi-squared and Cronbach’s alpha tests, and small dependent samples were tested using T-test. The value of Cronbach’s alpha coefficient of 0.561 for the Abbey Pain Scale was considered acceptable. The score on the Abbey Pain Scale correlates significantly with the result of a standardized self-assessment of pain intensity (r = 0.739, p= 0.001). We conclude that the Abbey Pain Scale serves as a convenient tool for assessing pain intensity in patients with impaired communication, and its use is indirectly related to satisfactory analgesia, due to good metric characteristics of validity and reliability.
Bol koji proizlazi iz fizičke traume i kirurških zahvata je vrlo jak. U starijih bolesnika, osobito onih s oštećenom komunikacijskim ili kognitivnim oštećenjem, ovaj bol se rijetko ili nikada procjenjuje. Važnost procjene bola ogleda se u kvalitetnom nadzoru i adekvatnom liječenju koji smanjuju komplikacije i ubrzavaju oporavak. Cilj studije bio je utvrditi metrijske karakteristike (pouzdanost i valjanost) bola na populaciji starijih bolesnika sa smetnjama u komunikaciji u Hrvatskoj i pokazati povezanost između procijenjene razine akutnog bola i učinkovitosti analgezije. Uzorak se sastojao od 31 pacijenta starijeg od 65 godina hospitaliziranog nakon frakture butne kosti na Odjelu za traumatologiju Sveučilišta Sestre Milosrdnice u Zagrebu, Hrvatska. Za procjenu bola korišteni su Abbey skala bola i vizualna analogna ljestvica. Duševni status pacijenata ocijenjen je korištenjem ljestvice Mini-mentalnog stanja. Podaci su obrađeni koristeći Chi-kvadrat i Cronbachov alfa test, a mali ovisni uzorci testirani su pomoću T-testa. Vrijednost Cronbachovog alfa koeficijenta od 0,561 za Abbey ljestvicu smatra se prihvatljivom. Ocjena na ljestvici bola značajna je u korelaciji s rezultatom standardizirane samoprocjene intenziteta boli (r = 0,739, p = 0,001). Zaključujemo da Abbey skala bola služi kao prikladan alat za procjenu intenziteta bola u bolesnika s oštećenom komunikacijom, a njezina uporaba neizravno je povezana s zadovoljavajućom analgezijom zbog dobrih metričkih karakteristika valjanosti i pouzdanosti.
Bibliografske bilješke na kraju teksta.
Abstract ; Sažetak.
Keywords: Perioperativni bol -- Kirurško liječenje -- Starije osobe -- Procjena bola